The implementation of the online thesis supervision during pandemic covid-19 at one of graduate and postgraduate programs in Indonesia - Ujang Suparman (Universitas Lampung, 2021)
The Covid-19 pandemic has affected almost all departments, including academic activities, and almost all campuses have been locked down. One of the most affected by the covid-19 pandemic is the writing of scripts/theses or papers for short. The purpose of this research is to fill in the gaps. Although they cannot come to campus, they can still consult their papers and get feedback from their supervisors. To achieve this goal, the researcher has used advances in information, computers, and technology (ICT). However, even though the use of ICT has been widely used, including in universities, its use in the process of paper supervision is still very limited. By contrast, many students and lecturers in certain universities even before the outbreak of the Covid-19 pandemic, got difficulties to determine the right time for both parties to meet because of the affairs of the lecturers or students. The pandemic worsened the situation.The purpose of the research is to find a new effective strategy to supervise students in writing papers, especially during the Covid-19 pandemic. Therefore, there are three main sub-goals of the research: 1) To research on how to realize online-based paper supervision. 2) To trace students' opinions on the implementation of online paper supervision; and 3) To find new and effective ways of paper supervision. Questionnaires, interviews, and documents were used to collect data. People have found that using online is very effective and efficient in guiding paper writing. Students and lecturers can communicate via the internet anytime and anywhere, even if it is under the threat of the Covid-19 pandemic; the supervisor’s advice is easy for students to understand, easy to follow and tidy. More importantly, students' writing products are better, tidier and more comprehensive.